O anúncio publicitário no youtube: uma proposta de produção textual - Silva Júnior, Ivanildo Félix da (2017)
This work has as general objective to develop a didactic project aimed at amplifying the textual production skills of students of the 1st period of the Publicity and Advertising Course, from the production of the advertisement announcement in the Youtube support. As specific objectives, we intended: (I) Lead the students to know the sociocommunicative characteristics of the advertisement announcement in YouTube support; (II) Elaborate and apply a proposal of production of the advertisement announcement together with students of the Publicity and Advertising; (III) Analyze the textual production of the students, to verify which sociocomunicative characteristics of the advertisement announcement stood out in their productions. For realization of the proposed objectives, we are based on Research Action. Besides that, we adopted as methodological procedures: the bibliographical lifting and the application of a didactic project. The results demonstrate that the advertisement announcements produced by the students corresponded to the sociocommunication characteristics of this discursive genre. So much the announcements of the initial production, as the one of the final production corresponded to the analysis criteria proposed: consonance with the social function of the advertisement announcement, syntony with the thematic aspects of the genre, syntony with the uses of the language typical of the genre and mobilization of argumentative strategies typical of the announcement genre. In terms of conclusion, we highlight that, in YouTube support, the production of the advertisement announcement involves the uses of the speech. That does with that this genre stimulates the promotion of orality practices in the education extent. With the use of this discursive genre, we accomplished a work aimed at expanding the development of orality practices of the students involved in this project. With this, the acquired knowledges with the appropriation of the sociocommunicative characteristics of the publicity genre, especially the knowledge that alludes to the uses of speech and its formalities, can be used in students' daily practices. In this sense, contributing to the training of competent users of the language requests the teachers the realization of a work linked to the appropriation of the genres.